Liecību nolasīšana vai atskaņošana tiesā. Problēmas un to risinājumi - Ramata, Kristīne (Latvijas Universitāte, 2017)
Bakalaura darba nosaukums ir “Liecību nolasīšana vai atskaņošana tiesā. Problēmas un to risinājumi”. Šajā bakalaura darbā pētīta tiešuma un mutiskuma principa ievērošana tiesas spriešanā, aizstāvības tiesību īstenošana tiesā, liecinieku liecības nolasīšanas ticamība tiesā, Kriminālprocesa likuma 501. panta piemērošana tiesā, ievērojot apsūdzētā tiesības, kas garantētas Eiropas Cilvēktiesību un pamatbrīvību konvencijas 6.panta 3.punkta d) apakšpunktā. Liecību nolasīšanas pamati Latvijā tiek salīdzināti ar citu valstu liecību nolasīšanas vai atskaņošanas tiesā pamatiem.

The title of the Bachelor’s Paper is “Reading or Playing of Testimony in Court. Issues and Possible Solutions”. The research of this Bachelor’s Paper is devoted to the consideration of the principle of directness and oral hearing within the jurisdiction, the effectuation of the right to defense in court, the validity of reading witness testimonies in court, the application of the Section 501 of the Criminal Procedure Law, taking into consideration the rights of the accused, which are guaranteed by Subclause d) Clause 3 of Article 6 of the European Convention on Human Rights and Fundimental Freedoms. The basis of reading the witness testimonies in Latvia are compared with the basis or playing back the recordings of witness testimonies in other countries. Key words: Testimonies, witness, reading or playing back the recordings of witness testimonies in court, the principle of directness and oral hearing.
Reading or Playing of Testimony in Court. Issues and Possible Solutions
Keywords: Juridiskā zinātne; Liecinieks; Liecības; Liecību nolasīšana vai atskaņošana tiesā; Tiešuma princips; Mutiskuma princips